CTLA‐4 polymorphisms in Thai patients with rheumatoid arthritis, systemic lupus erythematosus, and systemic sclerosis. (17th September 2021) - Louthrenoo, Worawit; Kasitanon, Nuntana; Wongthanee, Antika; Kuwata, Shoji; Takeuchi, Fujio
Abstract: Aims: Studies on polymorphisms of the cytotoxic T lymphocytes associated antigen‐4 (CTLA‐4) genes in rheumatic disease patients are limited in Southeast Asia. This pilot study aimed to determine CTLA‐4 polymorphisms in Thai patients with rheumatoid arthritis (RA), systemic lupus erythematosus (SLE) and systemic sclerosis (SSc), and correlate them with serology. Method: One‐hundred RA, 70 SLE and 50 SSc patients, and 99 healthy controls (HCs) were included in this study. Polymorphisms of the CTLA‐4 gene at +49A/G, −318C/T, −1661A/G and −1722T/C loci were determined by polymerase chain reaction restriction fragment length polymorphism methods. Patient serum samples were determined as follows: RA (rheumatoid factor [RF] and anticyclic citrullinated peptide [anti‐CCP]), SLE (antinuclear antibodies [ANA], anti‐double‐stranded DNA [anti‐dsDNA], anti‐Smith [anti‐Sm], anti‐ribonucleoprotein [anti‐RNP], and anti‐Sjögren's syndrome antigen A [SSA]), and SSc (ANA, anti‐RNP, anti‐SSA, anti‐topoisomerase‐1 [anti‐Scl70], and anti‐centromere antibodies [ACA]). Results: Among the 4 loci studied (+49A/G, −318C/T, −1661A/G and −1722T/C) only the A allele frequency at the +49A/G was significantly higher in the RA patients than their HCs (47.25% vs 35.86%, P = .029, odds ratio [OR] 1.60; 95% CI 1.04‐2.47). It also was significantly higher in the subgroup of RA patients with positive RF and anti‐CCP than their HCs (47.50% vs 35.86%, P = .020, OR 1.62; 95% CI 1.06‐2.47 and 48.89% vs 35.86%, P = .012, OR 1.71; 95% CI 1.11‐2.64, respectively). No polymorphisms at these 4 loci were observed in SLE or SSc patients. Conclusion: The A allele at +49A/G locus of the CTLA‐4 gene was associated with RA in Thais.